(untitled) (World of finance, 2019)
Introduction. Scarce local budget financial resources, lack of sufficient transparency of budget expenditures, and poor quality of public services provided by the central and local governments - all these factors require comprehensive governance reforms introduction primarily budget reform and powerdecentralization reform. Purpose. The aim of the article is to identify special traits and discover challenges of the local budgets planning and execution system, to analyze potential approaches to its improvement based on outcomes and effects of budget reform and local self-government reform implementation in Ukraine. Results. The article summarizes the tasks, measures and achievements of the local budgets reform and intergovernmental relation reform. The changes in the local budget revenue and expenditure structure were analyzed taking into account recent amendments to Budget and Tax Codes of Ukraine. The local budgets planning methods and approaches as well as procedures for fiscal equalization ofthe local government’s financial capacity were investigated; 2010-2017 reporting data on budget revenue and expenditures performance were analyzed. At the same time the article determines key budget parameters preliminarily included in draft 2018 Budget Law and medium-term Budget Declaration, in particular regarding local budgets and intergovernmental transfers and also represents review of progress achieved under the territorial communities’ amalgamation and establishment of direct interrelation between central government and newly formed amalgamated communities. Conclusion. According to the results ofthe research and analysis, the article substantiates the necessity of further local budget revenue amplification, the expediency of the budget decentralization considering budget subsidiarity principle, as well as the effectiveness of the new interbudgetary relation model.